Middle Childhood Feelings Toward Mothers: Predictions From Maternal Directiveness at the Age of Two and Respect for Autonomy Currently. Issue 3 (4th January 2015) - Ispa, Jean M.; Carlo, Gustavo; Palermo, Francisco; Su‐Russell, Chang; Harmeyer, Erin; Streit, Cara
Abstract The goals of this study were to examine (1) stability of maternal directiveness during interactions with their children from toddlerhood to late middle childhood, (2) direct and mediated relations between mothers' directiveness when children were two years old, mothers' respect for autonomy and children's positivity and negativity toward their mothers when children were in late middle childhood, and (3) differences in these paths by ethnoracial group. Participants included 876 European‐American, 789 African‐American, and 411 Mexican‐American mothers and their children from the Early Head Start Research and Evaluation Project. Maternal respect for autonomy at Time 2 partially mediated an association between Time 1 directiveness and observed child positivity toward mothers at Time 2. There was also a direct inverse link between Time 1 maternal directiveness and children's observed positivity toward mothers at Time 2. Relations were similar across ethnoracial groups and for boys and girls. The discussion focuses on heterotypic stability in directive parenting and its implications for children's feelings toward their mothers.